Análise da vida remanescente de uma viga de rolamento - Gustavo Costa Avila (2016)
This study examines the fatigue life of a Melt Shop crane girder with over 30 years of operation. Research indicates that the most frequent failures in these structures is related to fatigue in welded joints, thus an initial approach was performed according to AASHTO standard for calculating the remaining fatigue life of the structure. The alternating stress at themost severe loading conditions was obtained by numerical simulation in ANSYS software. Based on history and production forecasts, each critical welded joint fatigue life was determined. To calibrate the model, it was performed a field test with strain gages t determinate the real stress variation during plant regular operation. At this stage, crane load was parameterized in the computational model and varied to simulate the real behavior of the structure under the measured stresses. The analysis pointed out the most critical points which guided a visual inspection that identified cracks that could lead to a structural collapse. Identified cracks growth was simulated through FRANC2D software that applies the LEFMmethod to determine the stress intensity factor. The calculated values were used to reach fatigue life for crack growth from an initial to a critical value that is expected to lead to a brittle fracture. It was concluded that the S-N method associated with finite element analysis has proven an efficient technique for determining the most critical structure joints damage reducing inspection work significantly. The application of linear elastic fracture mechanics techniques reached more conservative results. This technique can assist maintenance crew in determining inspection intervals and the best moment for intervention to repair existent cracks based in their calculated remaining life.